Subspecific taxonomy of African porcupines Hystrix spp.: is there anything beyond the species level? - Mori, Emiliano; Sogliani, Davide; Senini, Caterina; Laurenzi, Alessandro; Viviano, Andrea; Cianferoni, Fabio (Zootaxa, 2021)
Taxonomy is a mistreated matter, but its role in ecology, behaviour and conservation studies is pivotal. Disentangling amongst different subspecies is challenging given the high arbitrariness level in determining thresholds of genetic and morphological distances. Splitting frenzy trends have increased the number of animal taxa and for most of them a critical redefinition is required. In this work, we reviewed knowledge and validity of subspecific taxa identified for African crested porcupines Hystrix cristata and Hystrix africaeaustralis. In the past, several subspecies were recognized for both the species, but successive works suggested H. cristata and H. africaeaustralis as monotypic species with no clear explanation. Recently, the validity of the taxon H. cristata senegalica has been claimed again. We analysed all available data and discussed all the subspecific taxa in light of both genetic and morphological data. We revalidated here the synonymy Hystrix senegalica Cuvier, 1823 = Hystrix cristata Linnaeus, 1758. Syn. rev. Two names are treated as nomina dubia: Acanthion daubentonii Cuvier, 1823 (formalization) and “Hystrix capensis Gr.”. Hystrix cristata var. alba de Sélys-Longchamps, 1839 has been deleted from the synonymic list of H. cristata. Neither mitochondrial nor nuclear DNA data militate for the existence of any subspecific taxon, although further data are required for H. cristata from East Africa (e.g., Kenya and Tanzania). Similarly, morphology seems to play for a clinal variation in both species. For available data, we thus strongly recommend to keep both H. cristata and H. africaeaustralis as monotypic species.